Obturator neuropathy combined with Guillain-Barre syndrome - Macit, Ça?lar; Taner, Neda; Eyüpoğlu, Ozan Emre (Istanbul Medipol University, 2020)
Obturator neuropathy caused by entrapment of obturator nerve is a disease with numbness, pain and weakness in legs. Guillain-Barre syndrome is an immune-me-diated peripheral polyneuropathy characterized by nearly same symptoms. 51-year-old man presented with severe shortness of breath. He was admitted to ICU and treated with mechanical ventilation followed complete blood count (CBC). We observed inflammation, started required medications and, we provided improvement in a short time. When patient was visited, he explained numbness, pain in hip area, muscle weakness in all extremities. Cervical MRI and nerve conduction tests were performed. MRI showed oedema in sciatic nerve and entrapment of obturator canal, resulted to obturator neuropathy and nerve conduction tests revealed GBS. He was treated with plasmapheresis and IVIG, he was discharged without neurological recovery. The patient consent was taken orally. In conclusion, treatments decreased complaints and provided to walk short distances. Reinnervation signals were observed in nerve conduction test.
Keywords: Guillain-Barre Syndrome; Obturator Neuropathy; IVIG; Nerve Conduction Test